Reevaluating the Alliance–Outcome Relationship in the Early Sessions of Cognitive Behavioral Therapy of Depression. (May 2021) - Whelen, Megan L.; Murphy, Samuel T.; Strunk, Daniel R.
The therapeutic alliance has been reliably associated with outcome across psychotherapies. We investigated the alliance–outcome relationship in the early sessions of cognitive behavioral therapy of depression using a model that disaggregates within- and between-persons variance while estimating the reciprocal relation between variables. We used this model in a combined data set from two studies totaling 191 patients. In our primary model, we found evidence for a predictive within-patients relationship between alliance and symptoms such that symptoms predicted regressed change in alliance and alliance predicted regressed change in symptoms. In a more conservative detrended model, these relationships were not significant. Given that (a) most of the variability in alliance scores is between patients, (b) the size of the alliance–outcome relationship is modest, and (c) the alliance–outcome relationship is not robust to detrending, our findings suggest that alliance plays at most a small role in improving patient outcomes in cognitive behavioral therapy of depression.